The Role of Parents with Blind Disabilities in Forming Disiplined and Independent Characters in Elementary School-aged Children - Armaini Armaini; Nurhastuti Nurhastuti; Setia Budi (Institut Agama Islam Negeri Palopo, 2022)
Discipline and independence are qualities that children should have. These characters will be very useful to support children's learning progress. This, of course, must be supported by parents, who are the main support system for children. However, their roles will be very different and become an exception for parents with blind disabilities. This study aims to find out how the role of blind parents develops the character traits of discipline and independence in their children. This study uses a qualitative narrative method. This research was conducted in a family with the characteristics of parents who are blind disabilities, and children who are without blind disabilities. This research was conducted in 2021 in one of the sub-districts in the city of Padang. Data collection techniques include interviews, observation, and documentation. The results of the study show that the character of discipline can be exercised by establishing disciplinary behavior in children by setting their bedtimes well and then giving clear and consistent rules. Meanwhile, independent character can be used to familiarize children with daily activities such as bathing, eating, dressing, washing, praying, and doing schoolwork.